Meningkatkan Kecintaan Budaya Lokal melalui Pelatihan Membaca Naskah Kuno Beraksara Pegon di Kampus IAIN Syekh Nurjati Cirebon - Fika Hidayani; Am'mar Abdullah Arfan (Yumary: Jurnal Pengabdian kepada Masyarakat, 2023)
Purpose: Improving local culture by preserving heritage from the ancestors namely manuscripts and improving skill of reading manuscripts in Pegon script. Methodology: The training was held online and attended by 34 participants, 31 participants from students, and 3 participants from lecturers. The method consists of lectures, questions and answers; demonstrations, and practice, by first identifying the problem to formulate the form of the training to be carried out. Results: The training participants consisted of 5 majors, namely Arabic Language and Literature, Islamic History and Culture, Al-Qur'an Studies and Tafsir, the Islamic Community Development Department, and the Social Sciences Education Department. The participants are from Islamic boarding schools and public schools background and have the ability to speak the Javanese language or not. This is to group the training which consists of elementary and intermediate classes. As a result, the ability to read Pegon's script texts is increased, so that they can independently research Pegon's script directly to explore the contents of manucripts. Conclusion: The training activities went well. It is hoped that after participating in this training, participants will be able to independently learn to read Pegon texts through digital manuscripts on internet pages that provide digital manuscripts for free so that they continue to practice reading and become fluent.